Estudo comparativo entre ressecção e eletrocoagulação endometrial em paciebtes com sangramento uterino anormal - Elias, Leonardo Vieira [UNESP] (2014)
Purpose of the study. Compare the results of two techniques of endometrial ablation first generation. Type of study. Prospective, longitudinal and analytical study (Canadian Task Force II-2). The study site. Tertiary public hospital, university teaching center. Patients and methods. During the period October 2011 to September 2013, 73 patients with a history of abnormal uterine bleeding (AUB) and poor response to medical treatment for a minimum period of 12 months, were randomized and underwent endometrial ablation with monopolar resection electrode handle U followed by rollerball electrocoagulation with the group a (36 patients) with rollerball electrocoagulation only in group B (37 patients). The women were followed for an average period of 359 days (280;751) and 370 days (305;766), respectively. Interventions. The patients were submitted to endometrial ablation technique according to each group. Ratings at 30, 90, 180 and 360 days were accomplished through research protocol, which sought to assess the pattern of bleeding, associated symptoms, failure rate and satisfaction rate. Results. The groups were homogeneous clinical and epidemiologically (P ≥ 0.05). Surgical time and the volume of distension medium used were lower in group B patients [mean of 48.5 (±12.0) vs. 31.9 (±5.6) minutes; P < 0.001 and 5.700 mL vs. 3.500 mL; P < 0.01]. There was a significant improvement in clinical symptoms after endometrial ablation in both groups, reducing the number of bleeding days (P < 0.01), as well as the number of pads used on the day of the flow rate (P < 0.01) and throughout the menstrual cycle (P < 0.01). There was also a lower incidence of surgical site infection in group B (30.5% vs. 8.1%; P < 0.05). The hysterectomy rate observed in the study was 9.6%, due to technical difficulties and intraoperative hemorrhage, persistence of SUA, development of incapacitating dysmenorrhea and / or pelvic pain ...